Macrophage Paired Immunoglobulin-Like Receptor B Deficiency Promotes Peripheral Atherosclerosis in Apolipoprotein E–Deficient Mice - Su, Wenhua; Liang, Liwen; Zhou, Liang; Cao, Yu; Zhou, Xiuli; Liu, Shiqi; Wang, Qian; Zhang, Hong (Frontiers in Cell and Developmental Biology, 2022)
Background: Peripheral atherosclerotic disease (PAD) is the narrowing or blockage of arteries that supply blood to the lower limbs. Given its complex nature, bioinformatics can help identify crucial genes involved in the progression of peripheral atherosclerosis. Materials and methods: Raw human gene expression data for 462 PAD arterial plaque and 23 normal arterial samples were obtained from the GEO database. The data was analyzed using an integrated, multi-layer approach involving differentially-expressed gene analysis, KEGG pathway analysis, GO term enrichment analysis, weighted gene correlation network analysis, and protein-protein interaction analysis. The monocyte/macrophage-expressed leukocyte immunoglobulin-like receptor B2 (LILRB2) was strongly associated with the human PAD phenotype. To explore the role of the murine LILRB2 homologue PirB in vivo, we created a myeloid-specific PirB-knockout Apoe−/− murine model of PAD (PirBMΦKO) to analyze femoral atherosclerotic burden, plaque features of vulnerability, and monocyte recruitment to femoral atherosclerotic lesions. The phenotypes of PirBMΦKO macrophages under various stimuli were also investigated in vitro. Results: PirBMΦKO mice displayed increased femoral atherogenesis, a more vulnerable plaque phenotype, and enhanced monocyte recruitment into lesions. PirBMΦKO macrophages showed enhanced pro-inflammatory responses and a shift toward M1 over M2 polarization under interferon-γ and oxidized LDL exposure. PirBMΦKO macrophages also displayed enhanced efferocytosis and reduced lipid efflux under lipid exposure. Conclusions: Macrophage PirB reduces peripheral atherosclerotic burden, stabilizes peripheral plaque composition, and suppresses macrophage accumulation in peripheral lesions. Macrophage PirB inhibits pro-inflammatory activation, inhibits efferocytosis, and promotes lipid efflux, characteristics critical to suppressing peripheral atherogenesis.